The encounter between biopolitics and constitutional law (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The article analyses the relationship between biopolitics and constitutional law. From the point of view of constitutional theory, the microphysics of power is full of conceptions of law and, specifically, of sovereignty, law, constitutions and the subject. It reaches biopower starting from war, moving through dominations, and ending with the governmentality of the population. But in the meantime constructs and overturns a doctrine of the State. From the perspective positive law, the point is to measure the constitutional text with the categories of biopolitical thought, such as government, the disciplinary normation and the normalization of the security and the population.
Keywords: Biopolitics; constitutional theory; sovereignty; governmentality; population